The European Union in multi-crisis: towards differentiated legal integration? - Tosiek, Piotr (Review of European and Comparative Law, 2022)
The aim of this article is to present a general forecast of the development of processes of legal integration in the European Union in the coming years. The European Union is in ‘multi-crisis’, which may force the member states to adopt an organizational development scenario based on differentiation. The selectivity of this differentiation is understood both in terms of the heterogeneity of integration in some areas and the reduction in the number of states fully participating in integration. An analysis of the current trends and solutions proposed and taken by EU decision-makers shows that the EU legal system is not subject to federalization, but in fact the tendency to deepen integration does not conflict with intergovernmentalism. The multiplicity of problems resulting from the multi-crisis will most likely require the deepening of the current differentiation mechanisms and the emergence of new ones.